The Introduction of F_____ to St. James's. - (:unkn) unknown (Sherlock, A., 1786)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1760-1820; St. James?s Palace; Fitzherbert, Maria Anne, 1756-1837